Dental anxiety and potentially traumatic events: a cross-sectional study based on the Tromsø Study-Tromsø 7 - Hege Nermo; Tiril Willumsen; Kamilla Rognmo; Jens C. Thimm; Catharina Elisabeth Arfwedson Wang; Jan-Are Kolset Johnsen (BMC, 2021)
Abstract Objective The objectives of the study were to describe the prevalence of dental anxiety and the possible associations between dental anxiety and potentially traumatic events in an adult population. Method The study is based on cross-sectional questionnaire data from the 7th wave of the Tromsø Study, a study of the adult general population in the municipality of Tromsø carried out in 2015-2016. The Modified Dental Anxiety Scale was used to measure dental anxiety across potentially traumatic events, oral health, dental attendance (avoidance) and current mental health symptoms (Hopkins Symptom Checklist). Individuals with high and low dental anxiety scores were compared to investigate differences in the distribution of potentially traumatic events, current mental health symptoms, avoidance, sex and oral health, and hierarchical multivariable regression was used to study the influence of traumatic events on dental anxiety. Results High dental anxiety was reported by 2.9% of the sample and was most prevalent among females and in the youngest age groups. Individuals with high dental anxiety reported more current mental health symptoms, and they were more likely to report poorer oral health and more irregular dental visits compared to individuals with no or lower dental anxiety scores. Concerning traumatic events, the reporting of painful or frightening dental treatment showed the biggest difference between those with high dental anxiety and low dental anxiety scores (a moderate effect). The hierarchical regression model indicated that reporting sexual abuse, traumatic medical treatment in hospital and childhood neglect significantly predicted dental anxiety in the step they were entered in, but only sexual abuse remained a significant individual contributor after controlling for current mental health symptoms. Conclusions The prevalence of high dental anxiety was lower than expected (2.9%), but dentally anxious individuals expressed a high burden of mental health symptoms, poor oral health and the avoidance of dental care. The regression analysis indicated that experiences with sexual abuse could affect dental anxiety levels in the absence of generalised symptoms of anxiety and depression.